Representation of Spouse Intimacy in Drake Doremus' Film Entitled Zoe - Assyamsi, Kinasih Ahya Fauzi; Wirawanda, Yudha (Universitas Muhammadiyah Surakarta, 2023)
Artificial intelligence has become a significant factor in every aspect of life, including health, education, and being a life partner for people. Researchers wanted to know how humans and artificial intelligence interacted, particularly in intimate relationships. This discovery raises the topic of how to best depict the closeness between humans and artificially intelligent machines. This study uses the qualitative method and the interpretive critical paradigm to investigate the behaviors and attitudes of a cultural group. This research uses Vetere’s intimacy theory as a concept Hall’s representation analysis and Roland Barthes' semiotic analysis that explore denotation and connotation. Data validity is ensured through triangulation analysis, which merges data from various sources for comparison. Self-disclosure involves personal information sharing, trust is built through non-verbal interactions, and commitment is shown through long-term actions such as gift-giving, gratitude, extending an invitation for a holiday, sexual activities, reassurances, providing assistance, and attention to detail. In conclusion, AI can develop further, one of which is developing emotions to establish closer relationships with humans. This can be proven by several results that have been mentioned. Future studies should investigate how feelings of love or emotion may be programmed into robots or artificial intelligence to create romantic relationships with humans.